Synthesis Of Chitosan-Activated Carbon Composites Using Hydrophilic Imidazolium-Based Ionic Liquids For Adsorption Of Acid Blue 25 Dye, Cd(ii) And Pb(ii) From Aqueous Solutions - Olalekan, Saheed Ismaila (2022)
Chitosan is a promising adsorbent for the removal of contaminants but its instability in acidic medium limits its potentials, and therefore its modification is necessary. Green synthesis approach featuring one pot mixture of chitosan (Ch) and activated charcoal (AC) in some selected hydrophilic imidazolium based ionic liquids (ILs) medium was utilised to modify chitosan into chitosan/activated carbon composite powders, beads and sponges. The prepared composites was utilised for the adsorption of acid blue 25 dye (AB25), Cd(II) and Pb(II) ions from aqueous solutions. Some selected hydrophilic imidazolium ILs including 1-allyl-3-methylimidazolium bromide (AmimBr), 1-allyl-3-methylimidazolium chloride (AmimCl), 1-ethyl-3-methylimidazolium acetate (EmimAc) and 1-butyl-3-methylimidazolium acetate (BmimAc) medium were utilised for the modification. The possible morphological and structural variation with respect to adsorptive characters and stability of the prepared composites were examined using scanning electron microscope (SEM), energy dispersive x-ray spectrometer (EDX), Brunauer–Emmett–Teller (BET) analysis, Fourier transform infrared (FTIR) spectrometer, x-ray diffraction (XRD) analysis and thermogravimetric analysis (TGA).